Effects of classical antiepileptics on thresholds for phenomena induced by cortical stimulation in rats - Haugvicová, R; Bílková, E; Kubová, H; Mares, P (The Journal of pharmacy and pharmacology, 2002)
Our aim was to study the effects of phenobarbital, phenytoin and ethosuximide on epileptic afterdischarges induced by cortical stimulation in rats. Fifteen-second series of low-frequency (8 Hz) rhythmic stimulation of the sensorimotor cortex were applied in rats with chronically implanted electrodes. Intervals between the stimulation series were at least 10 min and intensity was increased in a step-wise manner. Threshold current intensities were estimated for movements directly induced by stimulation, epileptic afterdischarges of the spike-and-wave type, clonic seizures accompanying this type of afterdischarge and transition into the limbic type of afterdischarge. Phenobarbital, phenytoin and ethosuximide were administered intraperitoneally before the first stimulation series. Phenobarbital (20, 40 and 80 mg kg(-1)) significantly increased the thresholds for the first three phenomena in a dose-dependent manner. Transition into the limbic afterdischarge was influenced only by the highest dose. Phenytoin (60 mg kg(-1)) only increased the thresholds insignificantly and ethosuximide (125 mg kg(-1)) was ineffective. We concluded that our model is useful for testing anticonvulsant effects. Results with three antiepileptic drugs correspond with their efficacy against myoclonic seizures in man.
Keywords: Animals; elektrická stimulace; Electric Stimulation; Ethosuximide; Rats, Wistar; Seizures; Electroencephalography; Electrophysiology; Anticonvulsants; lidé; Phenobarbital; Epilepsies, Myoclonic; ethosuximid; antikonvulziva; fenobarbital; epilepsie myoklonické; Male; modely nemocí na zvířatech; Phenytoin; Disease Models, Animal; krysa rodu Rattus; elektrofyziologie; zvířata; mužské pohlaví; elektroencefalografie; fenytoin; Rats; záchvaty; potkani Wistar; Humans